Contaminations in water distribution systems: a critical review of detection and response methods - Palma, Ludovica; Hatam, Fatemeh; Di Nardo, Armando; Prévost, Michèle (Aqua (London, England), 2024)
Water distribution networks play a crucial role in delivering safe water to communities. However, their extensive reach and complex structure make them susceptible to contamination. The development of efficient contamination warning systems (CWSs) can enable the monitoring and control of abnormal events. In an efficient CWS, several key aspects must be addressed: identifying potential contaminations that can occur, determining the most effective water parameters to monitor, and defining where these parameters can be strategically monitored. In the present study, literature articles will be analyzed to explore different parameters for detecting anomalies, assess the information they provide, and highlight the benefits of combining various parameters. Moreover, attention will be given to the definition of sensor placement, emphasizing the lack of attention in the literature for defining sensors’ detection thresholds. Finally, the study underscores that ensuring human safety requires not only prompt intrusion detection but also the implementation of corrective and preventive actions capable of mitigating contaminant spread through WDNs.